The mechanism for the electrooxidation of procarbazine pharmaceutical preparation in alkaline media and its mathematical description - V. V. Tkach; S. C. de Oliveira; S. K. B. de Oliveira; R. Ojani; O. V. Elenich; P. I. Yagodynets (Chimica Techno Acta, 2016)
The mechanism for the electrooxidation of procarbazine in alkaline media has been proposed. The process is realized completely on the electrode surface and is adsorption-controlled. The oscillatory behavior in this case is more probable, than for neutral media and may be caused by the influences of electrochemical oxidation and salt dissolution from the electrode surface.